2010
DOI: 10.1128/jb.00223-09
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosis High-Affinity Iron Importer, IrtA, Contains an FAD-Binding Domain

Abstract: Iron is an essential nutrient not freely available to microorganisms infecting mammals. To overcome iron deficiency, bacteria have evolved various strategies including the synthesis and secretion of high-affinity iron chelators known as siderophores. The siderophores produced and secreted by Mycobacterium tuberculosis, exomycobactins, compete for iron with host iron-binding proteins and, together with the iron-regulated ABC transporter IrtAB, are required for the survival of M. tuberculosis in iron deficient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 32 publications
1
104
0
Order By: Relevance
“…Shown are mean values (Ϯ standard deviations) from three experiments. grin compared to wild-type strains (29,41). The streptonigrin MIC for the ⌬bfrB strain in 7H9 medium was 1.2 g/ml, whereas the MIC for the wild-type and complemented strains was 10 g/ ml, showing that the level of sensitivity to streptonigrin was highly elevated in the ⌬bfrB strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Shown are mean values (Ϯ standard deviations) from three experiments. grin compared to wild-type strains (29,41). The streptonigrin MIC for the ⌬bfrB strain in 7H9 medium was 1.2 g/ml, whereas the MIC for the wild-type and complemented strains was 10 g/ ml, showing that the level of sensitivity to streptonigrin was highly elevated in the ⌬bfrB strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether the C-terminal catalytic domain is located in the cytosol or the periplasm, Chp2 was also expressed in M. smegmatis as a theophylline-inducible C-terminal fusion to either alkaline phosphatase (AP) or ␤-galactosidase (␤Gal), as has been performed previously to determine mycobacterial protein topology (Fig. 5C) (36)(37)(38). No AP activity was detected when Chp2 was expressed as the full-length protein, the N terminus (N-term), or the catalytic domain (cat) (Fig.…”
Section: Complementary Results Were Obtained By Tlc and Phosphorimagementioning
confidence: 99%
“…The ATP-binding cassette iron-regulated transporter IrtAB is involved in the uptake of cMBT across the inner membrane (29). Furthermore, as the N-terminal domain of IrtA binds flavin adenine dinucleotide (30), it was suggested that the iron in Fe-cMBT is reduced, as it is imported into the cytoplasm. This observation is consistent with the recycling of cMBTs, which would require a reductive iron release mechanism (1), rather than enzymatic degradation of the iron-loaded siderophores (5).…”
Section: Discussionmentioning
confidence: 99%
“…and cMBT (Fe-cMBT) are acquired by Mtb by a process dependent on the ESX-3 secretion system (18, 47) (omitted for clarity) likely involving a siderophore receptor. Iron is dissociated from cMBT by IrtAB concomitant with its import (29,30). Iron is dissociated from MBT by a reductive process (31) at a yet-to-be-determined subcellular location.…”
Section: Methodsmentioning
confidence: 99%